Penerapan Metode Waterfall Dalam Rancangan Sistem Informasi Manajemen Kartu Induk Retribusi (KIR) Berbasis Website - Fitra Kasma Putra (STMIK Budi Darma, 2022)
The UPTD of the Department of Transportation (Dishub) has one task, namely to carry out motorized feasibility tests or what is often called the KIR Test. This is done to ensure that motorized vehicles are roadworthy and ensure safety. In the operational activities in the service at the UPTD, there is a problem in the input process for the Retribution Master Card which is still being carried out using Microsoft Access. This, of course, slows down the work of managing user retribution card data. With these problems, the authors provide a solution that can help the relevant agencies in managing the levy master card into an integrated system based on the website. In this study the author uses the waterfall method in software development. The waterfall method is considered capable of solving a complex problem. Then in modeling the structure of the software the author uses UML (Unified Modeling Language) modeling. The result of this research is to create an information system that can facilitate UPTD in managing the master card when conducting motorized feasibility testing